Synthesis and Characterization of PMMA-PS Blend with Various Bi₂O₃ Nanoparticle Additives: Structural, Optical, Electrical, and Biological Properties - Nooralhuda J. Abd Ulkadhem; Mohsin K. Al-khaykanee; Maher Hassan Rasheed; Qasim Shakir Kadhim (Academia Open, 2026)
General Background: Polymer-based nanocomposites have attracted significant attention due to their multifunctional properties and broad applicability in advanced materials science. Specific Background: Blending polymethyl methacrylate (PMMA) and polystyrene (PS) with bismuth oxide (Bi₂O₃) nanoparticles provides a promising route to develop materials with combined structural, optical, electrical, and biological functionalities. Knowledge Gap: However, systematic understanding of how varying Bi₂O₃ nanoparticle concentrations affect the multifunctional properties of PMMA-PS nanocomposites remains limited. Aims: This study aims to synthesize PMMA-PS/Bi₂O₃ nanocomposite films with different nanoparticle loadings (0, 1, 3, and 5 wt%) and evaluate their structural, optical, electrical, and antibacterial characteristics. Results: The findings reveal uniform dispersion of Bi₂O₃ nanoparticles, reduced optical bandgap from 2.9 to 2.6 eV, increased refractive index, and improved DC electrical conductivity due to enhanced charge carrier mobility. Additionally, nanocomposites containing 5 wt% Bi₂O₃ exhibit strong antibacterial activity against Staphylococcus aureus and Escherichia coli. Novelty: This work demonstrates a comprehensive correlation between nanoparticle concentration and multifunctional performance in PMMA-PS/Bi₂O₃ nanocomposites. Implications: The developed materials show potential for applications in optoelectronic devices, humidity sensing, biomedical technologies, and environmental systems. Highlights: • Uniform Nanoparticle Dispersion Confirmed by Structural and Morphological Characterization• Optical Bandgap Reduction Accompanied by Refractive Index Increase• Highest Nanoparticle Loading Exhibits Strong Antibacterial Performance Keywords: PMMA PS Bi2O3 Nanocomposites, Optical Bandgap, Electrical Conductivity, Antibacterial Activity, Polymer Blends.